Effect of light backscattering from anterior segment structures on automated flare meter measurements. Issue 4 (July 2022) - Hasanreisoglu, Murat; Kesim, Cem; Yalinbas, Duygu; Yilmaz, Mervenur; Uzunay, Nur Sena; Aktas, Zeynep; Halim, Muhammad Sohail; Sepah, Yasir J; Nguyen, Quan Dong; Sahin, Afsun
Background: To evaluate effect of maximal anterior cortical lens density, iris scatter and anterior chamber depth on laser flare photometry. Methods: Patients diagnosed with clinical uveitis were enrolled in the study. Clinical flare gradings were recorded upon the Standardization of Uveitis Nomenclature. Aqueous flare was measured with an automated device (Kowa FM-700). Back-scattering from anterior cortical lens and anterior iris surface was calculated from Scheimpflug images. A curvilinear regression model was used to calculate estimated values for each clinical grade. These values were used to split cases in Group I (laser flare photometry lower than estimated) and Group II (laser flare photometry higher than estimated). Mean anterior chamber depth, pupil aperture, maximal anterior cortical lens density and iris scatter values were compared between two groups. A stepwise multiple regression analysis was performed to determine the effect of clinical flare gradings and ocular parameters on aqueous flare measurements. Results: The study included 228 eyes of 114 cases. Scheimpflug images were obtained from 105 eyes. Estimated aqueous flare measurements (in photons/milliseconds) were 4.87, 8.50, 14.81, 25.83, 45.04 and 136.93 for 0, 0.5+, 1+, 1.5+, 2+ and 3+ clinical flare respectively. Group II had higher maximal anterior cortical lens density than Group I (96.6 ± 37.1 vs 77.9 ± 17.1 pixel unit, p = 0.001). The measured aqueous flare was significantly related to clinical flare, maximal anterior cortical lens density and pupil aperture (adjusted R 2 : 0.480, p < 0.001). Conclusion: The back-scattered light from anterior cortical lens could affect laser flare photometry measurements. This effect might be quantified by Scheimpflug imaging.